High prevalence of accelerated silicosis among gold miners in Jiangxi, China - Tse, Lap Ah; Li, Zhi Min; Wong, Tze Wai; Fu, Zhen Ming; Yu, Ignatius Tak Sun (American journal of industrial medicine, 2007)
Background Accelerated silicosis has become uncommon in developed countries, whereas serious health threat still exists in small‐scale mining in developing countries. This study was to investigate the prevalence and risk factors of accelerated silicosis among Chinese gold miners. Methods A cross‐sectional medical examination was conducted among 574 Chinese gold miners. All participants were male rock‐drillers. The concentrations of total dust and quartz content were obtained from the government documentations. Descriptive data analyses were performed. Results The prevalence of accelerated silicosis was 29.1% (95% CI: 24.8–33.4%, 167 cases) after an average of 5.6 years of dust exposure, and a history of tuberculosis seemed to increase the risk. The concentration of respirable silica dust was estimated to be 89.5 mg/m3 (ranged: 70.2–108.8) in the underground goldmine, far exceeding the permissible exposure limits. Conclusions This study illustrates a serious health threat to small‐scale goldmine in China and indicates an urgent need for environmental control and disease prevention. Am. J. Ind. Med. 50:876–880, 2007. © 2007 Wiley‐Liss, Inc.